KELUARGA SEBAGAI AGEN UNTUK MEMBENTUK ANAK YANG SUPUTRA MENURUT AJARAN AGAMA HINDU - Kartika, I Gusti Ayu Nyoman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2013)
Having good kids is a great desire for every parent. It is, however, having good kids, not an easy one, that there are many things should be paid attention especially their education. Even, in this current globalization era. In accordance with developed knowledge and technology, human beings especially kids are quickly affected by information which is so easy for them to have it from mass media and internet, although it is not appropriate time for them but they do. This is the problem faced by every family in this globalization era like now. This is due to globalization flow brought positive matters, but also negative ones. If the families are not ready to face it and have no clear attitude, so a quick flow of globalization will affect them automatically. So here the role of parents as the first and main educators is so important. Because kids are asset of families. Parents must be aware and must take care their kids if they would like to have good kids (good and strength kids), especially its education problem. This is due to education to be the main requisite for competent and strong generation in the middle of globalization now. All of us are aware that in the future we will not be able to rely on natural resources only, if we are not able to manage it. That is why we (parents) prefer to give knowledge or education instead of hectares of rice field if they do not have skills. It is correct that people say, the family is the eldest agent of education in informal and natural one in having good kids (good and honorable kids) according to Hindu perspective.